Dispensasi Nikah di Pengadilan Agama: Tinjauan Maqosid Syariah dan Pertimbangan Maslahah-Mafsadah - Sainul, Ahmad (Islamic Family Law Department, STAI Syekh Abdur Rauf Aceh Singkil, Indonesia, 2024)
Changes to the marriage law regarding the age of marriage no. 1 of 1974 that the minimum age for men and women is 19 years and women are 16 years, so that men and women have a minimum age of marriage of 19 years, in article 7 paragraph 1 number 16 of 2019. However, there is a gap for underage children to be able to carry out marriages at the Religious Affairs Office through permission from the Religious Court, this is called a marriage dispensation. This article examines the urgent reasons for obtaining permission from the Religious Court for marriage dispensations and how Maqosid As-Syariah analyzes marriage dispensations. This paper uses qualitative methods of document study and in-depth descriptive-normative analysis. The research results show that there are several urgent reasons to obtain permission from the Religious Court, such as intimate relations, pre-pregnancy, mutual love and arranged marriage. The judge considers underage marriages which are prohibited in accordance with the applicable regulations according to the circumstances of the case, through maslahah and mafsadat, considering which is less detrimental. [Perubahan undang-undang perkawinan mengenai usia pernikahan no 1 tahun 1974 bahwa pria 19 tahun dan wanita 16 tahun minimal, menjadi pria dan wanita minimal usia perkawinannya menjadi 19 tahun, pada pasal 7 ayat 1 nomor 16 tahun 2019. Meski demikian adanya celah untuk anak yang dibawah umur dapat melaksanakan pernikahan di Kantor Urusan Agama melalui izin Pengadilan Agama, hal tersebut dinamakan dispensasi nikah. Tulisan ini mengkaji apa alasan mendesak untuk mendapatkan izin Pengadilan Agama terhadap dispensasi nikah dan bagaimana analisis Maqosid As-Syariah dalam mengkaji dispensasi nikah. Tulisan ini menggunakan metode kualitatif studi dokumen dan analisis deskriptif-normatif secara mendalam. Hasil penelitian menunjukkan ada beberapa alasan mendesak untuk mendapatkan izin di Pengadilan Agama seperti hubungan intim, hamil duluan, saling mencintai dan perjodohan. Hakim mempertimbangkan pernikahan dibawah umur yang dilarang sesuai aturan yang berlaku dengan keadaan kasus yang terjadi, melalui maslahah dan mafsadatnya yang mepertimbangkan mana yang lebih sedikit mudhoratnya].